Application of iron‐cobalt‐copper (Fe‐Co–Cu) trimetallic nanoparticles on anaerobic digestion (AD) for biogas production - Jadhav Pramod, Chandrakant; Zaied, Khalid; Krishnan, Santhana; Bhuyar, Prakash; A. W., Zularisam; Abdul Syukor, Abd Razak; Mohd Nasrullah, Zulkifli (Springer, 2022)
Anaerobic digestion (AD) is a commercial technology for bioenergy technology, which is a naturally occurring process of various microbial actions that break down organic waste materials and produce energy as biogas. Nevertheless, AD efficiency can be reduced due to substrate loading, ammonia inhibition, low methane yield, and impure feedstock. The supplementation of various metal nanoparticles (NPs) has shown significant results for higher biogas production in the AD process. Iron (Fe)–based NPs are an essential complement to microbes for higher biogas production in the AD process. In this study, Fe-Co–Cu TMNPs were synthesized via the chemical co-precipitation method using metal salt (Fe(NO3)3, Co(NO3)2, Cu(NO3)2), and precipitants. The structure and morphology of the TMNPs are characterized by Fourier-transformation (FTIR) spectroscopy, X-ray diffraction (XRD), and field-emission scanning electron microscopy (FESEM/EDX). Furthermore, the effect of Fe-Co–Cu trimetallic nanoparticles (TMNPs) in five different concentrations (0, 10, 20, 30, 40, and 50 mg/L) on palm oil mill effluent (POME)–based AD process for biogas production. The results showed that biogas yield increased by 5.66%, 7.54%, and 11.11% when using 20, 30, and 50 mg/L Fe-Co–Cu TMNPs. With the same TMNP concentration (10 mg/L and 40 mg/L), biogas yield was reduced by 26.41% and 11.11%, respectively. The economic feasibility and sustainability of Fe-Co–Cu TMNPs manufacturing and applying Fe-Co–Cu TMNPs in the AD process have been demonstrated. The assay showed the negative and positive effects of Fe-Co–Cu TMNPs in the POME-based AD process. The result of the present study indicates a possible new strategy for the preparation and design of NPs to enhance biogas production.